2019
DOI: 10.1016/j.ekir.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Subnormothermic Oxygenated Perfusion Optimally Preserves Donor Kidneys Ex Vivo

Abstract: Introduction The current methods of preserving donor kidneys in nonoxygenated cold conditions minimally protect the kidney against ischemia-reperfusion injury (IRI), a major source of complications in clinical transplantation. However, preserving kidneys with oxygenated perfusion is not currently feasible due to the lack of an ideal perfusion mechanism that facilitates perfusion with blood at warm temperature. Here, we have designed an innovative renal pump circuit system that can perfuse blood or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 17 publications
0
29
0
1
Order By: Relevance
“…Subsequently, both kidneys were nephrectomized, and the donor animal was euthanized. Autologous blood used for perfusion was collected via cannulation of the inferior vena cava before and after clamping the renal pedicles [ 23 ]. Blood collected prior to clamping is referred to as non-stressed blood, because there is no interruption of the blood flow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, both kidneys were nephrectomized, and the donor animal was euthanized. Autologous blood used for perfusion was collected via cannulation of the inferior vena cava before and after clamping the renal pedicles [ 23 ]. Blood collected prior to clamping is referred to as non-stressed blood, because there is no interruption of the blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…The dose of AP39 was chosen based on a previous in vivo murine transplantation study by our group [ 10 ]. The kidneys were perfused using an ex vivo pulsatile perfusion apparatus ( Figure 1 B), which was identical to the setup used in a previous study by our center [ 23 ]. Through adjusting the flow, the mean perfusion pressure was maintained at 60 mmHg after an initial 5-min period of gradual increase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent porcine transplant study by Bhattacharjee et al [50] reported that a perfusion temperature of 22 • C resulted in significant improvements on IRI injuries in SCS treated kidneys in terms of histology, suppression of expression of IRI related Toll-like receptor signalling molecules (MyD88, NF-kB and HMGB1), and graft functions, such as increase in urinary output and maximal renal blood flow compared to MP at 15 • C and 37 • C. While it was accepted that a hypothermic temperature may be optimal for the protection of metabolic energetic status and viability of kidney grafts, effects of subnormothermia on tissue ATP remains to be established in comparison to other more extensively studied temperatures.…”
Section: The Effects Of Higher Perfusion Temperatures (>4-10 • C) On mentioning
confidence: 99%
“…Indeed, both acellular and cellular perfusates have been used, showing that subnormothermic perfusion without an oxygen carrier is feasible [57,58]. Until now, subnormothermic kidney preservation has only been tested in DCD models of ex situ perfusion of pig kidneys [57][58][59][60]. Hoyer et al found improved kidney function after subnormothermic compared to oxygenated hypothermic kidney perfusion [60].…”
Section: Subnormothermic Kidney Perfusionmentioning
confidence: 99%